Recurrence patterns of sinonasal cancers after a 5‐year disease‐free period. (22nd February 2019) - Kim, Shin Ae; Chung, Yoo‐Sam; Lee, Bong Jae
Abstract : Objectives/Hypothesis: Sinonasal cancers are rare but have a poor prognosis. Most previous studies of these cancers have focused on 5‐year disease‐free survival, but recurrences are also known to occur after this period. We examined the post–5‐year recurrence patterns in sinonasal cancer patients by histologic type to determine the indicators for extended and close follow‐up requirements. Study Design: Retrospective chart review. Methods: A cohort of 241 sinonasal cancer patients was included. Demographic data, cancer site and stage, pathology and treatment results, and follow‐up and survival data were collected. Results: Of the 241 patients, a complete remission occurred in 163 (72.4%) patients, but 83 (50.9%) of these cases developed recurrence, which occurred beyond the 5‐year follow‐up period in 19 cases (11.7%). The most common post–5‐year recurrences were adenoid cystic carcinoma (six patients, 33.3%), followed by melanoma (three patients, 21.4%), poorly differentiated carcinoma (two patients, 18.2%), squamous cell carcinoma (six patients, 6.7%), and olfactory neuroblastoma (no patients, 0%). Post–5‐year local recurrence was highest in adenoid cystic carcinoma (six patients, 33.3%), followed by melanoma (three patients, 21.4%), poorly differentiated carcinoma (two patients, 18.2%), and squamous cell carcinoma (five patients, 5.5%). Post–5‐year regional recurrence occurred in one squamous carcinoma patient (1.1%), and distant metastasis was seen in one adenoid cystic carcinoma patient (5.5%). Conclusions: Sinonasal cancer shows an 11.7% recurrence rate after a 5‐year disease‐free period. As this recurrence pattern varies by tumor pathology, a specific follow‐up plan is needed for each cancer type. Level of Evidence: 3 Laryngoscope, 129:2451–2457, 2019